2008
DOI: 10.1186/1471-2164-9-493
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional response of Mexican axolotls to Ambystoma tigrinum virus (ATV) infection

Abstract: BackgroundVery little is known about the immunological responses of amphibians to pathogens that are causing global population declines. We used a custom microarray gene chip to characterize gene expression responses of axolotls (Ambystoma mexicanum) to an emerging viral pathogen, Ambystoma tigrinum virus (ATV).ResultAt 0, 24, 72, and 144 hours post-infection, spleen and lung samples were removed for estimation of host mRNA abundance and viral load. A total of 158 up-regulated and 105 down-regulated genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 53 publications
(57 reference statements)
2
35
0
Order By: Relevance
“…Ranaviruses persist and propagate through complex interactions between host cells and immune responses (Grayfer et al 2015). Cotter et al (2008) reported >100 up-and down-regulated genes in A. mexicanum following exposure to ATV. Some proteins that are encoded by FV3 immune evasion genes include vIF-2a, vCARD, and dUPTase (Grayfer et al 2015).…”
Section: Figurementioning
confidence: 99%
“…Ranaviruses persist and propagate through complex interactions between host cells and immune responses (Grayfer et al 2015). Cotter et al (2008) reported >100 up-and down-regulated genes in A. mexicanum following exposure to ATV. Some proteins that are encoded by FV3 immune evasion genes include vIF-2a, vCARD, and dUPTase (Grayfer et al 2015).…”
Section: Figurementioning
confidence: 99%
“…Consistent with the notion that hosts mount broad infl ammatory responses to ranaviruses, a comprehensive microarray analysis of axolotls ( Ambystoma mexicanum ) infected with the Ambystoma tigrinum virus (ATV) revealed the upregulation of numerous hallmark pro-infl ammatory and innate immune gene components in the spleens and lungs of these animals (Cotter et al 2008 ). These genes included (but were not limited to) phagocytic receptors and intracellular components, cytokine signaling molecules, complement components, NADPH oxidase subunits (myeloid enzyme catalyzing the reactive oxygen antimicrobial response), and myloperoxidase (granulocyte enzyme catalyzing the production of hydrogen peroxide) (Cotter et al 2008 ).…”
Section: Urodel Amphibiansmentioning
confidence: 71%
“…These genes included (but were not limited to) phagocytic receptors and intracellular components, cytokine signaling molecules, complement components, NADPH oxidase subunits (myeloid enzyme catalyzing the reactive oxygen antimicrobial response), and myloperoxidase (granulocyte enzyme catalyzing the production of hydrogen peroxide) (Cotter et al 2008 ). In contrast to what has been observed in X. laevis infected with FV3 (Morales et al 2010 ;Morales and Robert 2007 ), no lymphocyte proliferation genes were upregulated in response to ATV infections (Cotter et al 2008 ). This lack of an efficient adaptive response in this species may explain why ATV is so lethal to urodels.…”
Section: Urodel Amphibiansmentioning
confidence: 99%
See 2 more Smart Citations